The Agribusiness Innovation Center of Mozambique : Developing Value Adding Market-led Post-harvest Processing Enterprises in Mozambique - Brethenoux, Julia; Costa, Carlos; Giddings, Steven; Olafsen, Ellen; Rebello, Mulweli; Thaller, Jim (World Bank, Washington, DC, 2014)
Agriculture and fisheries are the main pillars of Mozambique's economy, having contributed in the last few years to more than 25 percent of the gross domestic product (GDP) and around 7 to 11 percentage points of the rate of economic growth. Agricultural development in Mozambique has been part of the government agenda because it is crucial to reducing poverty within rural zones. The long-term strategy for the agricultural sector in Mozambique focuses on improving food security and reducing poverty by supporting efforts of the smallholders, as well as the private sector, governmental agencies, and nongovernmental (NGO) agencies to improve agricultural productivity, agro-processing activities, and marketing, while sustainably exploiting natural resources. The agro-industrial sector is an important part of the agricultural sector as a whole; the food industries, beverages, and tobacco are estimated to account for about 70 percent of the overall structure of the manufacturing sector in Mozambique. Yet in Mozambique, processing activities are far behind opportunities offered by the potential diversified production. Instead of a vibrant private sector, which is considered a prerequisite for fostering economic growth and social development for poverty reduction, Mozambique has a poor agribusiness environment where most of the enterprises are micro and informal. As a result, it is still very difficult to invest in agriculture and agribusiness, to develop small and medium-size enterprises (SMEs), and consequently, to create new jobs. However, there is potential for many value chains to support increased post-harvest processing in Mozambique, such as horticulture, animal feed, oilseeds, and nuts.